OPTIMALISASI MUATAN KONTAINER AGAR KAPAL FULL AND DOWN - Sutini -; Mokhamad Abrori (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2017)
In conducting the loading to be assured that all load space can be filled by the charge (full) or the vessel can load up to a maximum laden (down) to obtain the maximum freight. However, since certain forms of gasket load, often cannot meet the cargo load space, the other possibility is way less good compaction ring, and so a lot of load space is not charged. Load space is not fully charged so-called "broken stowage".To gain the maximum, and then each shipping company wants its ships carrying cargo to the maximum loading, in order to reach the condition of the ship called Full and Down. Full and down is a condition such as that the loading and unloading space can be met entirely by the charge and the time that the ship has a maximum permissible laden according to the shipping area. The full conditions and down somewhat difficult to obtain. Usually the full circumstances but not down, or vice versa in order to achieve the intent to use the space optimally. So is the percentage of broken stowage space hatch that cannot be filled by the charge.In the principle of loading, stowage broken it should be kept as small as possible. This can be done by: Using the load cargo filler (filler cargo) is by tucking cargo crates - small chest between the crate - big chest, or fill in the gaps with pieces by pieces of cargo, cargos in confinement, and others, implement good planning so that it can be anticipated for the possibility of causing broken stowage, loading supervision during implementation where workers were compacting the hold often works less well, because there is a tendency to do the work in order to finish quickly. With good supervision of the officer of the watch and guard the other, the workers are expected to work according to the loading plan that has been created by the ship. This is very helpful in reducing the broken stowage, the applicability of Use - charge (dunage) efficiently so as not to result in reduced capacity load space (hatch), the use of space hatch loading. Stowage adapted to this form factor is the volume of the room in m³ been effectively required to can tamp 1 charge.Keywords : Broken Stowage, Full and DownDalam melakukan pemuatan harus diusahakan agar semua ruang muat dapat terisi penuh oleh muatan (full) atau kapal dapat memuat sampai sarat maksimum (down), sehingga dapat diperoleh uang tambang yang maksimal. Namun demikian, karena bentuk paking muatan tertentu, sering muatan tidak dapat memenuhi ruang muat, kemungkinan lain adalah cara pemadatan yang kurang baik, sehinnga banyak ruang muat yang tidak terisi muatan. Ruang muat yang tidak terisi muatan disebut “ broken stowage ”.Untuk memperoleh keuntungan yang semaksimal, Maka tiap-tiap perusahaan perkapalan menginginkan kapal-kapalnya membawa muatan secara maksimal pula, sehingga tercapai kondisi kapal yang disebut Full and Down. Full and down adalah suatu kondisi pemuatan sedemikian rupa sehingga ruang muat seluruhnya dapat dipenuhi oleh muatan dan saat itu kapal memiliki sarat maksimum yang diijinkan sesuai dengan daerah pelayaran. Kondisi full & down tersebut agak sulit didapatkan. Biasanya keadaan full tetapi tidak down,atau sebaliknya agar tercapai maksud untuk menggunakan ruang secara maksimal. Jadi broken stowage adalah prosentase ruang palka yang tidak dapat diisi oleh muatan.Dalam prinsip pemuatan, broken stowage ini harus diusahakan sekecil mungkin. Hal ini dapat dilakukan dengan cara : Menggunakan/memuat muatan pengisi (filler cargo) yaitu dengan menyelipkan muatan peti-peti kecil diantara peti-peti besar, atau mengisi kekosongan dengan potongan-potongan muatan, muatan–muatan dalam kurungan, dan lain–lain. Melaksanakan perencanaan yang baik sehingga dapat diantisipasi adanya kemungkinan-kemungkinan yang menimbulkan broken stowage, Pengawasan pada waktu pelaksanaan pemuatan dimana buruh yang melakukan pemadatan dalam palka sering kali bekerja kurang baik, karena ada kecenderungan untuk melakukan pekerjaan agar cepat selesai. Dengan pengawasan yang baik dari perwira jaga dan petugas jaga lainnya, diharapkan para buruh bekerja sesuai dengan rencana pemuatan yang telah dibuat oleh pihak kapal. Hal ini sangat membantu dalam mengurangi broken stowage, penggunaan terap–muatan (dunage) secara efisien agar tidak mengakibatkan berkurangnya daya tampung ruang muat (palka), penggunaan ruang palka disesuaikan dengan bentuk muatan. Stowage faktor adalah volume ruangan dalam m³ yang diperlukan secara effektif untuk dapat memadatkan 1 muatan.Kata kunci : Broken Stowage, Full and Down